Public instruments to leverage private capital for green investments in developing countries - Nannette Lindenberg (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
Considerable amounts of capital will be necessary if a green transformation is to be financed in the coming years. This paper gives a short introduction to the challenge of mobilising the required resources, particularly from private and institutional investors. More specifically, it provides an overview of eight public leveraging instruments that can be used to leverage private capital for green investments in developing countries and emerging economies. It discusses the strengths and weaknesses of these instruments and gives an assessment of their potential for a broader use. Additionally, the paper argues that more data transparency and quantitative research are needed to better assess the implications of the use of these instruments. Finally, it points out research gaps and proposes ideas for further research. The paper concludes by giving some policy recommendations.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Klimawandel